1986
DOI: 10.1093/nar/14.9.3717
|View full text |Cite
|
Sign up to set email alerts
|

Target sites for the transposition of rat long interspersed repeated DNA elements (LINEs) are not random

Abstract: The long interspersed repeated DNA family of rats (LINE or LIRn family) contains about 40,000 6.7-kilobase (kb) long members (1). LINE members may be currently mobile since their presence or absence causes allelic variation at three single copy loci (2, 3): insulin 1, Moloney leukemia virus integration 2 (Mlvi-2) (4), and immunoglobulin heavy chain (Igh). To characterize target sites for LINE insertion, we compared the DNA sequences of the unoccupied Mlvi-2 target site, its LINE-containing allele, and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Usually, LINEs are termed silent "fossil DNA" without transcriptional potential and are widely used as markers in genetic and phylogenetic studies [52]. However, several studies have reported functional features of the LINE elements [46,47,53], including a strong association with apoptosis. The relevance of these DNA elements in beta cell destruction is at present unknown, and it cannot be ruled out that our findings represent a clone-specific phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, LINEs are termed silent "fossil DNA" without transcriptional potential and are widely used as markers in genetic and phylogenetic studies [52]. However, several studies have reported functional features of the LINE elements [46,47,53], including a strong association with apoptosis. The relevance of these DNA elements in beta cell destruction is at present unknown, and it cannot be ruled out that our findings represent a clone-specific phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…On the assumption that the 3' ends of all CR1 elements are indeed defined by the tandem octamers, it follows that target site preference may be a general feature of CR1 transpositions since, as noted above, a 20-bp window of modest sequence homology is apparent just downstream of the octamer repeat for the various CR1 elements (10). Preferred target sites have also been noted for other transposable elements (5,11,20).…”
mentioning
confidence: 85%
“…First, while most non-LTR retrotransposable elements end in a short poly(A) sequence, very few of these elements contain the appropriately positioned AAU AAA (or AUUAAA) sequence upstream of this tail to promote the cleavage and polyadenylation steps (33). Second, some of the poly(A) tails found at the 3Ј end of integrated copies are interrupted by other nucleotides that are difficult to explain by the random mutation of a poly(A) tail after insertion (18). Third, some non-LTR elements end in repeating units other than poly(A).…”
mentioning
confidence: 99%